2003
DOI: 10.1152/ajplung.00305.2002
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of collagen-binding heat shock protein 47 in murine bleomycin-induced pneumopathy

Abstract: Kohno. Increased expression of collagen-binding heat shock protein 47 in murine bleomycin-induced pneumopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 17 publications
5
36
0
Order By: Relevance
“…The present authors previously reported that regenerated type II pneumocytes in UIP start expressing type I procollagen through the induction of HSP47 and play an important role in the development of fibrosis [9]. Recently, the present authors have also shown that type II pneumocytes start expressing HSP47 as fibrosis proceeds, in a rodent BL-induced pulmonary fibrosis model [26]. These findings suggest that increased type II pneumocytes, in addition to myofibroblasts, contribute to the fibrotic process through the production of HSP47-induced type I procollagen and suggest that HSP47-positive type II pneumocytes might represent a suitable target for therapeutic strategies designed for chronic pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…The present authors previously reported that regenerated type II pneumocytes in UIP start expressing type I procollagen through the induction of HSP47 and play an important role in the development of fibrosis [9]. Recently, the present authors have also shown that type II pneumocytes start expressing HSP47 as fibrosis proceeds, in a rodent BL-induced pulmonary fibrosis model [26]. These findings suggest that increased type II pneumocytes, in addition to myofibroblasts, contribute to the fibrotic process through the production of HSP47-induced type I procollagen and suggest that HSP47-positive type II pneumocytes might represent a suitable target for therapeutic strategies designed for chronic pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…Similar to FKBP65, the collagen-specific chaperone, Hsp47, has also been shown to be upregulated in bleomycin-induced pulmonary fibrosis (Razzaque et al 1998a;Ishii et al 2003) and induced in a dose-dependent manner by TGF-␤1 in cultured collagen-producing cells (Yamamura et al 1998;Sasaki et al 2002). Consistent with this experimental data, both pulmonary and dermal fibrotic lesions in humans show an increased production of Hsp47 concomitant with that of collagen (Razzaque et al 1998b;Razzaque and Ahmed 2002).…”
Section: Discussionmentioning
confidence: 78%
“…We have recently shown in rodent bleomycin-induced pulmonary fibrosis model that type II pneumocytes in addition to myofibroblasts express HSP47 with the progression of fibrosis, while these cells didn't express HSP47 in the control lungs [13,14]. We also previously reported that regenerated type II pneumocytes in usual interstitial pneumonia express HSP47 [17,18].…”
Section: Introductionmentioning
confidence: 91%
“…HSP47 expression was upregulated in experimental animal models of fibrosis, including murine bleomycin-induced pulmonary fibrosis [13,14], rat peritoneal sclerosis [15] and carbon tetrachloride-induced rat liver cirrhosis [16]. In addition, we previously reported that the expression of human HSP47 was increased in the fibrotic lesions of idiopathic pulmonary fibrosis (IPF) [17,18], fibrotic transplanted kidney [19], and peritoneal sclerosis [20].…”
Section: Introductionmentioning
confidence: 99%